2021
DOI: 10.1038/s41598-021-82529-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of allele-specific expression of genes in the model diatom Phaeodactylum tricornutum

Abstract: Recent advances in next generation sequencing technologies have allowed the discovery of widespread autosomal allele-specific expression (aASE) in mammals and plants with potential phenotypic effects. Extensive numbers of genes with allele-specific expression have been described in the diatom Fragilariopsis cylindrus in association with adaptation to external cues, as well as in Fistulifera solaris in the context of natural hybridization. However, the role of aASE and its extent in diatoms remain elusive. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…98.8% of the coding sequences matched assembled transcriptome sequences at an average of 98.5% ± 2.5% nt identity (median 99.4%) (Supplementary Figure S3 ). These results are consistent with expression of both diploid alleles, supporting previous reports suggesting the absence of genome-wide silencing mechanisms in diatoms 2 , 22 , 23 .…”
Section: Resultssupporting
confidence: 92%
“…98.8% of the coding sequences matched assembled transcriptome sequences at an average of 98.5% ± 2.5% nt identity (median 99.4%) (Supplementary Figure S3 ). These results are consistent with expression of both diploid alleles, supporting previous reports suggesting the absence of genome-wide silencing mechanisms in diatoms 2 , 22 , 23 .…”
Section: Resultssupporting
confidence: 92%
“…Diatoms are single-celled plants, mainly photosynthetic eukaryotes, that account for approximately 40% of primary productivity in oceans. Phaeodactylum tricornutum is a typical model diatom. ZIF-8 and ZIF-67 are porous dodecahedral crystalline materials consisting of tetrahedral clusters of MN 4 (M = Zn­(II) in ZIF-8 and M = Co­(II) in ZIF-67) linked by the imidazolate ligand 2-methylimidazolate (mim). ZIF-8 and ZIF-67 are the most representative zinc-based and cobalt-based ZIFs, and both materials are also widely used to recover and remove pollutants in the ocean and other contaminated water (e.g., to prepare for reverse osmosis desalination and to remove uranium). , Different metal ions have caused these materials to have different properties: cobalt ions have a weaker coordination force with 2-methylimidazole than zinc ions .…”
Section: Introductionmentioning
confidence: 99%
“…Such differences could be related to a fine-tuning gene expression that can be due to allele-specific expression (ASE). Such phenomena have been recently described in P. tricornutum ( Hoguin et al, 2021 ). Such ASE genes were enriched in genes involved in catabolism processes including proteasome subunits proteins, and autophagy, in intracellular protein transport, exocytosis, and endocytosis ( Hoguin et al, 2021 ) that correspond to pathways identified in this study.…”
Section: Discussionmentioning
confidence: 67%
“…Such phenomena have been recently described in P. tricornutum ( Hoguin et al, 2021 ). Such ASE genes were enriched in genes involved in catabolism processes including proteasome subunits proteins, and autophagy, in intracellular protein transport, exocytosis, and endocytosis ( Hoguin et al, 2021 ) that correspond to pathways identified in this study. Moreover, it would also be interesting to study gene alternative splicing as it was reported previously that extensive alternative splicing was involved in the regulation of gene expression in response to nutrient starvation, suggesting that P. tricornutum used it to cope with environmental changes ( Rastogi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 67%